2023
DOI: 10.1136/bmjopen-2021-050164
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of human immunodeficiency virus (HIV) among pregnant women in Nigeria: a systematic review and meta-analysis

Abstract: ObjectiveTo estimate prevalence of HIV infection in Nigeria and to examine variations by geopolitical zones and study characteristics to inform policy, practice and research.MethodsWe conducted a comprehensive search of bibliographic databases including PubMed, CINAHL, PsycINFO, Global Health, Academic Search Elite and Allied and Complementary Medicine Database (AMED) and grey sources for studies published between 1 January 2008 and 31 December 2019. Studies reporting prevalence estimates of HIV among pregnant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…Maternal and cord 25(OH)D, 3-epi 25(OH)D 3 , and 24,25(OH) 2 D 3 levels were all positively correlated (r = 0.7, r = 0.84, and r = 0.81, respectively, with p < 0.0001 for all). This is consistent with what has been previously described [ 38 , 39 ]. Most mothers, 70.86%, had sufficient levels of 25(OH)D. In contrast, only 21.9% of the newborns had sufficient levels of 25(OH)D. The prevalence of maternal 25(OH)D deficiency and insufficiency was 8.6% and 20.6%, respectively.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Maternal and cord 25(OH)D, 3-epi 25(OH)D 3 , and 24,25(OH) 2 D 3 levels were all positively correlated (r = 0.7, r = 0.84, and r = 0.81, respectively, with p < 0.0001 for all). This is consistent with what has been previously described [ 38 , 39 ]. Most mothers, 70.86%, had sufficient levels of 25(OH)D. In contrast, only 21.9% of the newborns had sufficient levels of 25(OH)D. The prevalence of maternal 25(OH)D deficiency and insufficiency was 8.6% and 20.6%, respectively.…”
Section: Discussionsupporting
confidence: 94%
“…The prevalence of neonatal 25(OH)D deficiency and insufficiency was 30.6% and 47.5%, respectively. These observations suggest that there may not be an efficient transfer of 25(OH)D to the newborn or that there is an independent regulation of 25(OH)D in the mother and the newborn [ 38 , 39 ]. These observations between sufficient maternal 25(OH)D levels and deficient newborn 25(OH)D levels have been reported in several studies [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present prevalence is significantly lower compared to the 2016 and 2019 sentinel surveys with 5.75% and 4.26% respectively among pregnant women (12,13), including the results of studies which reported HIV prevalences of 5.70% (95% CI: 4.93-6.40), 6% (3.0-10.2%) and 7.8% respectively among pregnant women in Cameroon (1820). Furthermore, the respective prevalence rates of 9.2% and 7.22% reported in the countries of Chad and Nigeria are also of relevance (21,22). Our findings therefore reflect the declining trend of HIV among pregnant women in Cameroon (7.6% in 2009 to 2.9% in 2016 (19,23) and from 3.4% in 2018 to 2.1% in 2022 (24–26).…”
Section: Discussionmentioning
confidence: 99%